2017
DOI: 10.21897/rmvz.923
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la suplementación clinoptilolita corto plazo sobre la ganancia de peso en becerros Holstein

Abstract: Objective. To determine whether short term supplemantation at two levels (1 or 2 g/kg) of clinoptilolite (CLNP) in the colostrum of dairy calves had any effect on total weight gain (TWG) and mean daily gain of weight (mdwg). Materials and methods. A total of 24 clinically healthy calves without diarrhea were assigned in a subset of three major groups of calves were studied: group I (n=8) received colostrum with clnp at the rate of 1/kg started immediately following calving at 12 and 24 hours, for a total of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…This confirms the fact that high rates of clinoptilolite supplement to mycotoxin-containing diets of calves has no adverse effect on productivity and contributes to normalize the protein metabolism by improving the pre-gastric digestion in animals. Alic Ural & Ural [15] showed that the addition of the clinoptilolite via colostrum appeared to enhance ADG in newborn calves without having any observable adverse effect.…”
Section: Resultsmentioning
confidence: 99%
“…This confirms the fact that high rates of clinoptilolite supplement to mycotoxin-containing diets of calves has no adverse effect on productivity and contributes to normalize the protein metabolism by improving the pre-gastric digestion in animals. Alic Ural & Ural [15] showed that the addition of the clinoptilolite via colostrum appeared to enhance ADG in newborn calves without having any observable adverse effect.…”
Section: Resultsmentioning
confidence: 99%
“…At 90 days, the difference between groups was not significant (p < 0.1035) (E2/C = +7.19%) [69,70]. recently, Ural et al observed increased total weight and mean daily gain in calves that receive clinoptilolite (1 or 2 g/kg) in colostrum at calving, 12 and 24 h [71].…”
Section: Effects On Health Status and Growth Performancementioning
confidence: 99%
“…Las inconsistencias en los resultados pueden deberse, en parte, al nivel de zeolita utilizado y a la composición de la dieta empleada. La mayoría de los informes con resultados positivos son en dietas de moderado a bajo contenido de energía, suplementadas con zeolita en un rango de 1 a 5% de la materia seca (Ghaemnia et al, 2010;Goodarzi y Nanekarani 2012;Ural, 2014); mientras que, la información sobre la respuesta al uso de zeolitas en rumiantes consumiendo dietas de finalización altas en energía es limitada.…”
Section: Introductionunclassified